Pemanfaatan Instagram Sebagai Media Komunikasi Publik Pada Dinas Komunikasi dan Informatika Kabupaten Sragen - Damayanti, Septina; Riyanto, Buddy; Sarungu, Lukas Maserona (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The development of technology in the field of communication and information ledto the existence of a media designed for the purpose of sharing posts in the formof photos or videos with users. One of these media is Instagram, Instagram mediaallows users to be given the freedom to upload any posts that come from userswhich are then seen by their followers. The existence of Instagram also makes iteasier for organisations, agencies or companies to carry out the publikcommunication process in order to maintain a good correlation with thecommunity and build an organisational image. Diskominfo Sragen Regency is oneof the organisations that uses Instagram social media in the communicationprocess to the publik. publik. The purpose of this study is to describe the use ofInstagram as a Publik Communication Media at the Communication andInformatics Office of Sragen Regency. The method used in this research isdescriptive qualitative method. Data obtained through interviews with SragenRegency Diskominfo Staff, Instagram Managers and Instagram followers@kominfo.sragen. In addition, data was also obtained by observation anddocumentation. The use of Instagram as a public communication medium at theSragen District Communication and Information Center is informative,structurally effective, but still less effective in operating Instagram. An evaluationand improvement process is needed so that the public can continue to receive thelatest and complete information about Sragen Regency.Keyword : Public Communication, Instagram, Diskominfo Sragen Regency